(untitled) (Iranian Journal of Kidney Diseases, 2014)
This study was conducted to investigate the association between serum uric acid level and blood pressure in type 2 diabetes mellitus. Sixty patients with type 2 diabetes mellitus were enrolled to the study. None of the patients had a history of gout, were treated with allopurinol, or were treated with antihypertensive drugs previously. The mean duration of DM was 9.2 ± 4.9 years. The mean serum creatinine level was 0.98 ± 0.22 mg/dL, and the mean serum UA level was 4.4 ± 1.2 mg/dL. The mean protein level in 24-hour urine sample was 388 ± 22 mg/d. The mean systolic and diastolic blood pressure values were 133.0 ± 13.0 mm Hg and 84.0 ± 7.4 mm Hg, respectively. There was no significant difference in levels of serum uric acid, hemoglobin A1c, serum creatinine, proteinuria, or systolic and diastolic pressure between the men and the women. A significant positive correlation was seen between serum UA and systolic (r = 0.312, P = .02) and diastolic blood pressure (r = 0.297, P = .03). Results of this study suggest that serum uric acid had a strong association with levels of systolic and diastolic blood pressure in type 2 diabetic patients. More attention to the serum uric acid level and treatment of hyperuricemia could halt the progress of diabetic nephropathy.